Gender differences in peritoneal dialysis initiation in the US end-stage renal disease population. Issue 1 (January 2020) - Vogel, Savannah L; Singh, Tripti; Astor, Brad C; Waheed, Sana
Background: Overall, a disproportionately small number of end-stage renal disease (ESRD) patients start peritoneal dialysis (PD) in the United States compared to hemodialysis. Little is known about whether gender has an effect on the initial modality of renal replacement therapy utilized by patients; however, prior studies have demonstrated gender disparities in the diagnosis and treatment of various other health conditions, including kidney disease. Methods: Using data from the United States Renal Data System (USRDS), we estimated the proportion of patients utilizing PD as their initial dialysis modality between 2000 and 2014, adjusting estimates to the mean value of all covariates and compared these estimates for women and men. Results: We found that 7.9% of women and 7.5% of men used PD as their initial dialysis modality. The unadjusted odds ratio (OR) of women initiating PD as their initial modality compared to men was 1.04 (95% CI 1.02–1.05, p < 0.001). After adjustment for age, race, ethnicity, cause of ESRD, number of comorbidities, income, employment status, and timing of referral to nephrology, the difference was even more significant, with women being 12% (OR 1.12, CI 1.10–1.14, p < 0.001) more likely to initiate PD than men. However, within different subgroups, older women and women with higher number of comorbidities were less likely to be on PD than their male counterparts. Conclusions: Our results indicate that gender plays a role in the initial dialysis modality used by patients and providers should be cognizant of these gender differences. Further studies are needed to ascertain the cause of this observed difference.